P529Efficacy and safety of S-ICD implantation without use of defibrillation threshold testing: a retrospective multicentric observational study. (18th June 2020) - Ricciardi, D; Picarelli, F; Forleo, G B; Di Belardino, N; Bisignani, A; Bisignani, G; Santini, L; Lavalle, C; Pignalberi, C; Picarelli, S; Aurino, L; Creta, A; et al.
Abstract: Introduction: The subcutaneous ICD (S-ICD) is a valid alternative to transvenous systems (TV-ICD) for the treatment of life-threatening arrhythmias, and the extravascular position of the lead allows a significant reduction of the risk of infection. Current guidelines recommend defibrillation threshold testing (DFT) at the time of S-ICD implantation (class I). Although randomised trials have proven the safety of TV-ICD implantation with no DFT, it is unclear whether such an approach could be adopted for S-ICD as well. The PRAETORIAN score, based on post-implantation chest X-ray, can accurately predict a high defibrillation threshold after S-ICD implantation. The aim of this retrospective multicentre study was to evaluate the efficacy and safety of S-ICD implantation with no DFT. Methods: We enrolled 203 consecutive patients undergoing S-ICD implantation in six different centres between October 2012 and January 2019. It was left at discretion of the operator whether performing or not DFT at the time of the procedure. Baseline device settings were collected, and the PRAETORIAN score was retrospectively calculated whenever chest X-ray was available. Both remote or in-clinic device interrogation reports were systemically analysed, and all the shocks and arrhythmia episodes identified. All the patients provided consent form and ethical approval was obtained. Results: The population (mean age 57.6 ± 14.2) was divided in two groups, based on whether DFT was performed at the time of the S-ICD implantation: 72 patients (35.4%) underwent DFT (DFT+ group), while 131 patients (64.5%) did not (DFT- group). In the DFT- group, mean LVEF was lower (32 ± 8% vs 42 ± 17%, p < 0.0001) and prevalence of diabetes mellitus and atrial fibrillation higher compared to the DFT+ group (27.5% vs 13.9%, p = 0.04 and 38.9% vs 19.44%, p = 0.007; respectively). In addition, the indication for S-ICD was more frequently primary prevention in the DFT- vs DFT+ group (70.8% vs 90.8%, p = 0.0004; respectively). No differences in terms of device programming were identified between the two cohorts. The PRAETORIAN score was significantly higher in the DFT- vs DFT+ patients (50 ± 26 vs 36 ± 18, p = 0.032; respectively). After a median follow-up of … months, we observed 5 appropriate shocks in 3 patients from the DFT+ group vs. 15 shocks in 8 patients from the DFT- group (p = 0.81). All the life-threatening arrhythmias were successfully recognised and treated by the device. DFT was complicated by pulseless electrical activity in one patient. One patient in the DFT- group suffered from an episode of ventricular tachycardia requiring a total of 4 shocks for being terminated. Six patients in the DFT- group died for non-arrhythmic causes. On the Kaplan-Meier analysis, cumulative survival was comparable between the two groups (log rank p value = 0.13). Conclusions: This study suggests that implantation of S-ICD with no DFT might be reasonable. These results should be confirmed in prospective randomised trials.